2022
DOI: 10.1093/g3journal/jkac217
|View full text |Cite
|
Sign up to set email alerts
|

The cAMP-PKA pathway regulates prey sensing and trap morphogenesis in the nematode-trapping fungus Arthrobotrys oligospora

Abstract: Sensing environmental factors and responding swiftly to them is essential for all living organisms. For instance, predators must act rapidly once prey is sensed. Nematode-trapping fungi (NTF) are predators that use “traps” differentiated from vegetative hyphae to capture, kill, and consume nematodes. These traps undergo drastic and rapid morphological changes upon nematode induction. Multiple signaling hubs have been shown to regulate this remarkable process. Here, we demonstrate that the conserved cAMP-PKA si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…In the plant pathogen F. graminearum, double mutants of the PKA catalytic subunit-encoding genes cpk1 and cpk2 are severely defective in pathogenicity (Hu et al, 2014). Here, the results showed that ΔAoacy and ΔAopkaC1 mutants lost the ability to form traps and capture nematodes (Figure 2), which was consistent with the analysis in A. oligospora (strain TWF154); the absence of the PKA catalytic subunit Tpk2 (an orthologue of PkaC1) abolishes trap morphogenesis (Chen et al, 2022). Therefore, the cAMP-PKA signalling pathway is required for the morphogenesis of infection structures in NT fungi and other pathogenic fungi.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In the plant pathogen F. graminearum, double mutants of the PKA catalytic subunit-encoding genes cpk1 and cpk2 are severely defective in pathogenicity (Hu et al, 2014). Here, the results showed that ΔAoacy and ΔAopkaC1 mutants lost the ability to form traps and capture nematodes (Figure 2), which was consistent with the analysis in A. oligospora (strain TWF154); the absence of the PKA catalytic subunit Tpk2 (an orthologue of PkaC1) abolishes trap morphogenesis (Chen et al, 2022). Therefore, the cAMP-PKA signalling pathway is required for the morphogenesis of infection structures in NT fungi and other pathogenic fungi.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, mitogen‐activated protein kinase (MAPK) signalling and Ca 2+ ‐related signalling are involved in the regulation of trap formation and hyphal development (Kuo et al, 2020; Xie et al, 2021, 2022a; Jiang et al, 2022). Recently, a gene deletion mutant of the PKA catalytic subunit Tpk2 in A. oligospora was shown to be insensitive to nematode presence (Chen et al, 2022). However, the function of the cAMP‐PKA signalling pathway in A. oligospora and other NT fungi remains largely unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the amino acid sequences of spore-producing genes in model fungi such as the Aspergillus nidulans , Aspergillus fumigatus , and Neurospora crassa as references, the homologs of AosfgA and AofluG in A. oligospora were obtained through comparison using the NCBI database [ 36 ]. The physicochemical properties of individual amino acid sequences were calculated using ExPASy-ProtParam-tool, and the domains and functional sites of proteins were predicted using InterProScan.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we have demonstrated that AoRac and AoCdc42 play a crucial role in hypha growth, lipid accumulation, DNA damage, sporulation, trap formation, pathogenicity, and stress response ( Yang et al, 2022 ). Subsequently, the cAMP-PKA signaling pathway has been proven to be involved in hyphal growth, sporulation, trap morphogenesis, stress tolerance, and autophagy in A. oligospora ( Chen et al, 2022 ; Zhu et al, 2022b ). In addition, several genes are related to MAPK cascades, such as mkk1 (coding a MAP kinase kinase) and bck1 (coding a MAP kinase kinase kinase; Xie et al, 2021 ), ste7 (coding a MAP kinase kinase) and fus3 (coding a MAP kinase; Chen et al, 2021 ; Xie et al, 2023 ), hog1 (coding a MAP kinase; Kuo et al, 2020 ), and ime2 (coding a MAP kinase; Xie et al, 2020 ), which all participate in the development and pathogenicity of A. oligospora .…”
Section: Introductionmentioning
confidence: 99%